Georgia, the Peach State - Holtz, Eric Siegfried (Milwaukee, WI : World Almanac Library, 2002)
Illustrations and text present the history, geography, people, politics and government, economy, and social life and customs of Georgia.
Includes bibliographical references (p. 46) and index.
Keywords: Georgia -- Juvenile literature; Georgia